Graphite-Si-SiC ceramics produced by microwave assisted reactive melt infiltration. Issue 7 (July 2019) - Padovano, Elisa; Giorcelli, Mauro; Bianchi, Giovanni; Biamino, Sara; Rovere, Massimo; Tagliaferro, Alberto; Ortona, Alberto
Abstract: A novel microstructure of graphite-Si-SiC ceramics was successfully prepared by liquid silicon infiltration of graphite-based preforms; instead of using conventional methods, the reactive infiltration process was assisted by microwaves. The effects of microwave power variation on the microstructure and the mechanical properties of infiltrated materials were studied. X-ray diffraction and Raman investigations showed the presence of both unreacted graphite and Si in addition to SiC formed at their interface. The graphitic and silicon phases were separated by a SiC network, which results more homogeneous as microwave power was increased. The amount of SiC was found to be higher in function of the growing power level; a higher conversion of graphite into SiC yielded a more dense material. The bending strength measurements confirm this, showing higher values for the samples processed using a power level of 75% of the full power compared to those obtained with 30% and 60%.